2018
DOI: 10.1029/2018gl080382
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Characterization of Jupiter's Equatorial Disturbance Cycle

Abstract: We use an infrared data set captured between 1984 and 2017 using several instruments and observatories to report five rare equatorial disturbances that completely altered the appearance of Jupiter's equatorial zone (EZ): the clearance of tropospheric clouds revealed a new 5-μm-bright band encircling the planet at the equator, accompanied by large 5-μm-bright filaments. Three events were observed in ground-based images in 1973, 1979, and 1992. We report and characterize for the first time the entire evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 45 publications
11
31
0
Order By: Relevance
“…However, this relationship is not observed in our results, where both periodograms show a periodicity of 6.6±0.5 years south of the equator (number 5 in Figure 14 corresponding to EZ disturbance events, in agreement with Antuñano et al (2018)), and a peak at 7.4±1 years at the southern edge of the NEB, at 7-9 • N, in agreement with the ∼7-year periodicity observed on the changes of the equatorial wind profile at cloud level Simon-Miller and Gierasch, 2010;Tollefson et al, 2017). Nevertheless, Cosentino et al (2017) and Simon-Miller et al (2006) suggested the existence of two different periodicities of the QQO, with the period at ∼4 mbar being shorter than the period at ∼14 mbar, although more observational data would be needed to verify this.…”
Section: Periodogram Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…However, this relationship is not observed in our results, where both periodograms show a periodicity of 6.6±0.5 years south of the equator (number 5 in Figure 14 corresponding to EZ disturbance events, in agreement with Antuñano et al (2018)), and a peak at 7.4±1 years at the southern edge of the NEB, at 7-9 • N, in agreement with the ∼7-year periodicity observed on the changes of the equatorial wind profile at cloud level Simon-Miller and Gierasch, 2010;Tollefson et al, 2017). Nevertheless, Cosentino et al (2017) and Simon-Miller et al (2006) suggested the existence of two different periodicities of the QQO, with the period at ∼4 mbar being shorter than the period at ∼14 mbar, although more observational data would be needed to verify this.…”
Section: Periodogram Analysissupporting
confidence: 84%
“…and small periodic chevron-like features(Simon-Miller et al, 2012) are observed at its northern and southern edge, respectively. Additionally, a recent study byAntuñano et al (2018) has shown that the usually 5-µm-dark EZ undergoes strong variations every 6-8 years, where its appearance changes completely from the darkest region on Jupiter to a region with a bright band south of the equator and large bright filaments connecting the North Equatorial Belt and this new bright band (seeFigure 8a).InFigure 7awe represent the 5-µm brightness of the EZ, expandingFigure 2cin Antuñano et al (2018) to show the new data between August 2017 and July 2018. In Figure 7b the normalized brightness residuals are shown.…”
mentioning
confidence: 99%
“…Future missions to the ice giants must find a way to probe the circulation patterns below the top-most clouds of methane and H 2 S ice (e.g., . And continued monitoring of temporal variations and episodic outbursts in the belts and zones (Sanchez-Lavega et al 2018;Fletcher 2017;Antuñano et al 2018Antuñano et al , 2019 could reveal insights into the shifting balance between the meridional circulation cells, and the forces determining their quasi-periodic timescales.…”
Section: Discussionmentioning
confidence: 99%
“…The methane and microwave-brightness contrasts could be explained by single large-scale cells, with equatorial upwelling and polar subsidence. The inter-hemispheric transport could be a circulation pattern analogous to Earth's Brewer-Dobson stratospheric circulation (e.g., Andrews et al 1987), with air rising at low latitudes and descending at mid-to high-latitudes, inferred from the distribution of ozone and driven by planetary wave activity. The singlecell idea for the Ice Giants should be compared to the better-studied gas giants, where the moderate-scale temperature contrasts observed in the tropospheres of Jupiter and Saturn are superimposed onto larger-scale hemispheric asymmetries (Fig.…”
Section: Extension To the Ice Giantsmentioning
confidence: 99%
“…One was the surprising lack of cloud cover even in the southern part of the EZ that was relatively unaffected by the colouration event that started around that time (Antuñano et al, 2018), which was comparable in its thickness to that found in the northern NEB due to mixing from the North Tropical Zone (NTropZ). Surprisingly high chromophore abundances are retrieved in the northern half of the EZ, even though the colouration event was still in its infancy at this stage.…”
Section: Modelling Meridional Variations In Tropospheric Aerosol Strumentioning
confidence: 99%